Climate change What challenges for the South? - Janicot, Serge; Aubertin, Catherine; Bernoux, Martial; Dounias, Edmond; Guégan, Jean-François; Lebel, Thierry; Mazurek, Hubert; Sultan, Benjamin (Focus, 2015)
The mobilisation centred on the 2015 Paris Climate Conference (COP 21) is an opportunity to highlight the vulnerability of environments and populations in the South in the face of climate warming. Some tropical regions are already suffering from its effects, with heat waves in the Sahel, disturbances to monsoon systems, the melting of the Andean glaciers, threats to biodiversity, a rise in sea level and other features. Research conducted by IRD and its partners provides key knowledge for better understanding of the complexity of these phenomena. This book is a synthesis in three parts: observing and understanding climate change, analysing its main impacts on environments and setting societies and national public policies at the heart of the climate challenge. Focused on the capacity for resilience of populations and ecosystems in the face of trends in the climate, the book explores solutions that reconcile mitigation and adaptation in response to climate change, conservation of the environment and a reduction of inequalities. The work is both well documented and explanatory, reviewing operations and the results of research that is firmly involved and interdisciplinary, closely associating partners in the North and the South.